Ecological Literacy among Technical and Non-Techical Students of Nepal - Khanal, S.; Pandey, U.; Khan, I.A.; Mishra, S.; Kunwar, B. (Journal of Agriculture and Environment, 2020)
Ecological literacy creates foundation towards betterment of environment and reducing negative externalities of human activity. A study was done to evaluate the level of ecological literacy among students pursuing technical and non-technical education in Nepal. Structured questionnaire was designed, pilot tested and administered to different students all over Nepal through Google form. Altogether 375 responses were obtained. Gender, type of education and ethnicity significantly affected ecological literacy. Female students, technical students and elite groups’ students were 2.4%, 4.92% and 2.19% more ecologically literate than male students, non-technical students and marginalized group students respectively. Technical students have basic level and non-technical students have low level of ecological literacy. Though these groups of students are acquiring information from various courses they are studying, they were unable to relate what they learnt in class with their surroundings. Urgent and effective amendments and action is needed in developing sound scientific information about ecosystem, skills for critical thinking, positive attitude, creative and strategic problem solving to increase the rational action among the students to sustain the environment.